2016
DOI: 10.2139/ssrn.2815457
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Predictors of Student Mobility

Abstract: This paper analyses the determinants of student mobility under the unified system of admission in Russia and evaluates the barriers which still limit educational mobility. It is argued that even under the Unified State Examination (USE) and the decreased transaction costs of applying to universities, student mobility is directed towards more developed regional educational markets and richer regions, but is still limited due to the financial constraints in the absence of the additional student support. Russia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Another barrier to higher education is educational mobility. Although the introduction of USE increased the level of educational mobility of university applicants [Slonimczyk et al, 2017], in some cases family income and characteristics of regional socio-economic and educational development can have a strong influence on the decision to move and accordingly, on the accessibility of higher education in general [Prakhov, Bocharova, 2016;Anikina et al, 2014;Pitukhin, Semenov, 2011]. Finally, the characteristics of the family and regional factors are important predictors of university choice in the context of its selectivity (a choice of elite vs non-elite HEIs) [Prakhov, 2016a].…”
Section: Introductionmentioning
confidence: 99%
“…Another barrier to higher education is educational mobility. Although the introduction of USE increased the level of educational mobility of university applicants [Slonimczyk et al, 2017], in some cases family income and characteristics of regional socio-economic and educational development can have a strong influence on the decision to move and accordingly, on the accessibility of higher education in general [Prakhov, Bocharova, 2016;Anikina et al, 2014;Pitukhin, Semenov, 2011]. Finally, the characteristics of the family and regional factors are important predictors of university choice in the context of its selectivity (a choice of elite vs non-elite HEIs) [Prakhov, 2016a].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, in addition to microeconomic indicators (individual characteristics, family SES), macro-indicators, such as the average regional salary, affect salary expectations. Such variation in actual wages may contribute to the flow of students to regions with higher wages, and, as a result, will adversely affect future trends in regional development (for example, see Prakhov, Bocharova 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different countries have shown the greater importance of territorial characteristics (e.g., job market conditions) in attracting students, compared to other factors (e.g., university attractiveness), which are more closely related to keeping students in their comfort zone (Lörz et al, 2016;Prakhov & Bocharova, 2016). Consequently, Kim (2017) points out that academic capitalism intersects the old hierarchies in local areas (in terms of economic growth or labour market conditions) with new academic stratification (i.e., the reputation of universities).…”
Section: Being a Mover In The Italian He Systemmentioning
confidence: 99%